Chenopodium murale L.: A Weed of Medicinal Importance - A Brief Review - Tayyeba Rehman; Huma Rao (Tehran University of Medical Sciences, 2023)
Weeds are considered a great threat to crops. So weed eradication is an important task to increase crop yield. Chemical weed control in various crops decreases their nutritive potential. To overcome this problem to some degree, it is suggested to use these weeds instead of destroying them. Keeping this in view, such losses can be compensated by exploring their medicinal utility and identifying their future medicinal prospects. Chenopodium murale L. (Amaranthaceae) is an annual weed growing throughout the world. This review aims to summarize the reported pharmacology and phytochemistry of C. murale to explore its medicinal utility and identifying their future medicinal prospects. The review was done by literature collection from textbooks and online databases without a time limit. The weed name was confirmed by 'The Plant List'.  C. murale extracts, their isolated active constituents, and nanoparticles have been reported for various pharmacological actions like hepatoprotective, antihypertensive, antidiabetic, antidiarrheal, anticancer, antimicrobial, nematicidal, antioxidant, and cytotoxic. The pharmacological effects of C. murale may be due to the presence of secondary active metabolites such as phenolic acids, flavonols, terpenes and terpenoids, flavonoids and a steroidal glycoside. Reported phytochemistry and pharmacology suggest that C. murale could be an important medicinal agent for leishmaniasis, hypertension, infections and liver diseases. However, further studies are warranted.